Replanning Strategis Plan for Marketing Product with SWOT Analysis, QSPM, Marketing Mix 4P and KPI Methods During the COVID-19 Pandemic: English - Hartono, James Luis; Budiman, Irwan; Sembiring, Anita Christine (Journal Knowledge Industrial Engineering (JKIE), 2021)
UKM Prime Store operates as a retail store that sells various oils by taking oil from authorized oil distributors, distributing it to various motorbike repair shops and to as many agents as possible so that it reaches consumers. The strategic plan needs to be used due to the decline in market demand by 20% in 2019, where in 2018 2000 boxes were sold per month, but in 2019 only 1600 boxes were sold per month, in 2020 there was an increase of 10% at the beginning of the year to 1700- 1800 in January - June 2020, then decreased again until the end of 2020. The purpose of this research is to increase sales volume by utilizing technological advances, increasing sales through brochures and promotions. The methods used are the SWOT method, QSPM and the 4P method. From the strategic results obtained 6 strategies that can be used from QSPM data processing, it is hoped that UKM can increase sales by taking advantage of technological advances, and increase sales through brochures and promotions made by UKM. This research is expected to help companies and UKM affected by the pandemic to get up and increase the sales of their products again.